2020
DOI: 10.1111/his.14107
|View full text |Cite
|
Sign up to set email alerts
|

Perineural invasion by prostate adenocarcinoma in needle biopsies predicts bone metastasis: Ten year data from the TROG 03.04 RADAR Trial

Abstract: Aims Perineural invasion (PNI) by prostatic adenocarcinoma is debated as a prognostic parameter. This study investigates the prognostic predictive value of PNI in a series of patients with locally advanced prostate cancer treated with radiotherapy and androgen deprivation using 10 years outcome data from the TROG 03.04 RADAR trial. Methods Diagnostic prostate biopsies from 976 patients were reviewed and the presence of PNI noted. Patients were followed for 10 years according to the trial protocol or until deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Moreover, the 10-year follow-up analysis of the TROG 03.04 RADAR cohort have shown strong association between PNI and bone metastasis after radiation and ADT treatment [22].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the 10-year follow-up analysis of the TROG 03.04 RADAR cohort have shown strong association between PNI and bone metastasis after radiation and ADT treatment [22].…”
Section: Discussionmentioning
confidence: 99%
“…PNI is demonstrated in bone metastasis as well. A clinicopathological study reported that PNI is detected in 449 (46%) out of 976 patients with prostate cancer by diagnostic biopsies and importantly prostate cancer with PNI is significantly associated with increased development of bone metastasis compared to prostate cancer without PNI over 10 year follow-up interval [72] . Further, it is also described that PNI detected in the biopsy specimens is the most reliable predictive histopathological feature for bone metastasis, increasing the risk of bone metastasis 11-fold [73] .…”
Section: Pni and Bone Metastasismentioning
confidence: 99%
“…Interestingly, the clinical ramifications of the role of nerves in cancer go beyond treatment, as nerves could also be used to identify life‐threatening prostate cancers (that require aggressive therapeutic interventions) from indolent prostate cancers (that only require active surveillance). Nerve infiltration is indeed higher in high‐risk prostate cancer compared with low‐risk prostate cancer 31 and perineural invasion, which is associated with nerve infiltration, has recently been shown to be an independent predictor of metastatic progression in prostate cancer 36 . In addition, as nerve trunks in the prostate can be observed by using magnetic resonance imaging (MRI), nerve density determined by MRI could be a noninvasive way to identify aggressive prostate cancers at the time of diagnosis 37 .…”
Section: The Role Of Nerves In Cancermentioning
confidence: 99%
“…Nerve infiltration is indeed higher in high‐risk prostate cancer compared with low‐risk prostate cancer 31 and perineural invasion, which is associated with nerve infiltration, has recently been shown to be an independent predictor of metastatic progression in prostate cancer. 36 In addition, as nerve trunks in the prostate can be observed by using magnetic resonance imaging (MRI), nerve density determined by MRI could be a noninvasive way to identify aggressive prostate cancers at the time of diagnosis. 37 Thus, in clinical terms, nerve involvement could be used for the establishment of cancer prognosis, to predict patient outcome, and in the treatment for preventing or interfering with neurosignaling.…”
Section: The Role Of Nerves In Cancermentioning
confidence: 99%